2007
DOI: 10.1093/jn/137.4.855
|View full text |Cite
|
Sign up to set email alerts
|

Dietary (n-3) Fatty Acids and Brain Development1

Abstract: The (n-3) fatty acids are essential dietary nutrients, and one of their important roles is providing docosahexaenoic acid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
512
3
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 725 publications
(547 citation statements)
references
References 61 publications
(82 reference statements)
9
512
3
14
Order By: Relevance
“…As discussed by Smit et al (2013a), interpretation of effects of mLCPUFA treatment on survivability may be difficult due to confounding effects of gestation length and the use of induced farrowing, as was again the practice in the present trial. Although brain weight was not different between treatments (Smit et al, 2014), the DHA concentration in brain tissue was higher in stillborns from mLCPUFA-fed sows compared with controls, which is in agreement with other research (Rooke et al, 2000 and2001a), and was not surprising considering the importance of DHA for brain development (Innis, 2007). Higher DHA levels in the brain could lead to increased postnatal growth rates due to a change in behavior.…”
Section: Discussionsupporting
confidence: 90%
“…As discussed by Smit et al (2013a), interpretation of effects of mLCPUFA treatment on survivability may be difficult due to confounding effects of gestation length and the use of induced farrowing, as was again the practice in the present trial. Although brain weight was not different between treatments (Smit et al, 2014), the DHA concentration in brain tissue was higher in stillborns from mLCPUFA-fed sows compared with controls, which is in agreement with other research (Rooke et al, 2000 and2001a), and was not surprising considering the importance of DHA for brain development (Innis, 2007). Higher DHA levels in the brain could lead to increased postnatal growth rates due to a change in behavior.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, n-3 LCPUFA can influence postnatal growth rate and survival through a change in piglet behaviour. DHA is important for brain development (Innis, 2007) and in central dopamine metabolism (Ng and Innis, 2003), which in turn affects feeding behaviour (McEntee and Crook, 1991). Rooke et al (2001a) showed that inclusion of salmon oil (rich in n-3 LCPUFA) in the sow's diet decreased pre-weaning mortality from 11.7% to 10.2%, mainly because of a reduction in piglets crushed by the sow.…”
Section: Discussionmentioning
confidence: 99%
“…Arachidonic acid (ARA; c20:4 n-6), eicosapentaenoic acid (EPA; c20:5 n-3) and docosahexaenoic acid (DHA; c22:6 n-3) are long-chain polyunsaturated fatty acids (LC-PUFA) and well known to play important regulatory functions in the immune, nervous and cardiovascular system (Innis, 2007;Calder, 2009;Calder and Yaqoob, 2009;Russo, 2009). The n-6 LC-PUFA can be synthesized from linoleic acid (LA; c18:2 n-6) and those of the n-3 family from a-linolenic acid (ALA; c18:3 n-3).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in brain DHA concentrations have been demonstrated to be positively correlated with cognitive development (Innis, 2007). In addition, the dietary supplementation of DHA could improve the cognitive dysfunction due to aging (McCann and Ames, 2005;Cole and Frautschy, 2006).…”
Section: Introductionmentioning
confidence: 99%